Occupational Exposure to Diesel and Gasoline Engine Exhausts and the Risk of Kidney Cancer in Canadian Men. Issue 8 (30th July 2018) - Peters, Cheryl E; Parent, Marie-Élise; Harris, Shelley A; Bogaert, Laura; Latifovic, Lidija; Kachuri, Linda; Villeneuve, Paul J; ,
Abstract: Introduction: Kidney cancer is the fifth most common incident cancer in Canadian men. Diesel and gasoline exhausts are common workplace exposures that have been examined as risk factors for non-lung cancer sites, including the kidney, but limitations in exposure assessment methods have contributed to inconsistent findings. The objective of this study was to assess the relationship between occupational gasoline and diesel engine exhausts and the risk of kidney cancer in men. Methods: The National Enhanced Cancer Surveillance System (NECSS) is a Canadian population-based case–control study conducted in 1994–1997. Incident kidney cancer cases were identified using provincial registries, while the control series was identified through random-digit dialing, or provincial administrative databases. Self-reported questionnaires were used to obtain information on lifetime occupational history and cancer risk factors. Two hygienists, blinded to case status, coded occupational histories for diesel and gasoline exhaust exposures using concentration, frequency, duration, and reliability. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) separately by exhaust type. The separate and combined impacts of both engine exhausts were also examined. ORs were adjusted for age, province, body mass index, occupational secondhand smoke exposure, and education. Results: Of the kidney cancer cases ( n = 712), 372 (52%) had exposure to both exhausts at some point, and 984 (40%) of the controls ( n = 2457) were ever exposed. Workers who had ever been exposed to engine exhausts were more likely to have kidney cancer than those who were never exposed (OR diesel = 1.23, 95% CI = 0.99–1.53; OR gasoline = 1.51, 95% CI = 1.23–1.86). Exposure to gasoline exhaust was consistently associated with kidney cancer in a dose–response manner ( P value for trends in highest attained and cumulative exposure both <0.0001). Those men with high cumulative exposure to both gasoline and diesel exhaust had a 76% increased odds of kidney cancer (95% CI = 1.27–2.43). Conclusions: This study provides evidence that occupational gasoline, and to a lesser extent, diesel exhaust exposure may increase the risk of kidney cancer.